Differential geometry of the quantum 3-dimensional space - Çelik, SA; Yasar, E (INST PHYSICS ACAD SCI CZECH REPUBLIC, 2006)
A Hopf algebra structure of the extended three-dimensional quantum space is defined. A differential algebra of the extended three-dimensional quantum space is introduced and its Hopf algebra structure is explicitly given. The (undeformed) Lie algebra of three dimensional quantum space is obtained.
Keywords: quantum space; Hopf algebra; differential calculus; Lie algebra; Physics